Cross-sectoral collaboration as a solution: The preventative work against social exclusion in the municipal well-being plans for children and youth - Paavola, Kaisa (My University, 2015)
This study focuses on finding out about the wicked problems such as social exclusion and the prevention of it with the help of cross-sectoral collaboration. The aim of this study is to look into the measures the Finnish municipalities are planning to execute in order to promote inclusion and prevent exclusion for the children and youth and what kind of cross-sectoral collaboration is needed to do so. These measures are studied from the municipal well-being plans for children and youth in five different Finnish municipalities or regions. In the theoretical part the difficulty of wicked problems, in this case social exclusion, is cleared out and the development of the term and the mechanisms of the process of social exclusion are explained. Battling complex and multilevel problems such as social exclusion requires measures like cross-sectoral collaboration hence the authorities are unable to solve them just on their own. Shared knowledge, expertise and resources provide earlier and more extensive information of the overall situation of the individual in the risk of social exclusion and enable the earlier interference. Empirical part analyses the municipal well-being plans for children and youth in different parts of Finland: Espoo, Kainuu, Oulu, Pieksämäki and Salo. The framework of cross-sectoral collaboration is remodeled in order to categorize the challenges the municipalities face and the measures they execute and the future needs of the work for better well-being. The findings of the study state that the problems that the municipalities face are somewhat similar even the situation for the selected municipalities or regions is rather different. The measures municipalities offer to a solution are relevant but the need for better cross-sectoral collaboration and the emphasis on the earlier stage of support is clear.
Keywords: wicked problem; social exclusion; cross-sectoral collaboration; municipal well-being plans for children and youth; fi=Julkisjohtaminen: European Civil Servants - kansainvälisen hallinnon ohjelma|en=Public Management: European Civil Servants|